Transformasi Kebijakan Kesehatan Digital, Implementasi dan Tantangan: Studi Sistematic Review - Lubis, Ernawati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Digital health transformation is growing in various countries, but the need for this to improve access and quality of global healthcare services has not been thoroughly studied. This study aims to explore digital health transformation in various countries, including policy bases, implementation methods, challenges, and the impact of implementation on improving access and quality of healthcare services. This study used a Systematic Literature Review (SLR) approach guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The literature search was conducted through PubMed/MEDLINE, Scopus, Web of Science, ScienceDirect, and Google Scholar. Inclusion criteria were determined based on the PICOS framework, while data analysis was conducted through thematic analysis to identify policy trends, implementation successes, barriers, and impacts of digital health adoption. Findings indicate the existence of policies at the national, community, and healthcare levels, such as the WHO Global Digital Health Strategy 2020-2025, EU4Health, and interoperability guidelines (Health Level Seven, FHIR). Implementation includes eHealth in hospitals (EMR, OCS, PACS), smartphone-based mHealth, telehealth, and innovations such as the "Tess" chatbot, the M-TIBA financing platform, and HealthEmove. Key challenges include limited infrastructure and connectivity, disparities in access, lack of operational guidance, and reliance on cross-sector collaboration. Digital health transformation has the potential to improve universal coverage, effective health crisis management, service efficiency, and community engagement. However, technology and resource gaps require adaptive and inclusive policy strategies. Digital health is a strategic instrument for expanding access and improving the quality of global healthcare, but its successful implementation requires sustained strengthening of governance, infrastructure, and human resource capacity.